2008
DOI: 10.1007/s10778-009-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Quickest-descent curve in the problem of rolling of a homogeneous cylinder

Abstract: The motion of a heavy homogeneous cylinder is considered as rolling without slipping along an unknown curve. A functional in the form of the total time of rolling is found and minimized by solving a variational problem. The algebraic equation of the quickest-descent directrix is derived in parametric form Keywords: heavy homogeneous cylinder, rolling without slipping, variational problem, functional, quickest-descent directrixIntroduction. The main performance criterion for many vibration-protection devices, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
2
11
0
2
Order By: Relevance
“…In this connection, it is necessary to find the shape of the directrix of a cylindrical surface over which a heavy homogeneous cylinder rolls without slipping (pure rolling) in the least time. The requirement of no slipping is standard for vibration-protection problems.The present study continues the research reported in [4,5] where the following differential equation of brachistochrone along which a cylinder rolls without slipping (Fig. 1) was for the first time derived by setting up and minimizing a functional T z x [ ( )]: ( )[ ( ) ] ( ) z C z r z C + + ¢ -+ ¢ = 1 1 2 2 1 , z zx z L L ( ) , ( ) 0 0 = = .…”
supporting
confidence: 91%
See 3 more Smart Citations
“…In this connection, it is necessary to find the shape of the directrix of a cylindrical surface over which a heavy homogeneous cylinder rolls without slipping (pure rolling) in the least time. The requirement of no slipping is standard for vibration-protection problems.The present study continues the research reported in [4,5] where the following differential equation of brachistochrone along which a cylinder rolls without slipping (Fig. 1) was for the first time derived by setting up and minimizing a functional T z x [ ( )]: ( )[ ( ) ] ( ) z C z r z C + + ¢ -+ ¢ = 1 1 2 2 1 , z zx z L L ( ) , ( ) 0 0 = = .…”
supporting
confidence: 91%
“…The present study continues the research reported in [4,5] where the following differential equation of brachistochrone along which a cylinder rolls without slipping (Fig. 1) was for the first time derived by setting up and minimizing a functional T z x [ ( )]: ( )[ ( ) ] ( ) z C z r z C + + ¢ -+ ¢ = 1 1 2 2 1 , z zx z L L ( ) , ( ) 0 0 = = .…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This is because over time, these structures wear out and may require urgent restoration for (i) reduction of the dynamic loads on these structures and (ii) strengthening of their load-carrying components. Here we address only case (i) and propose a new engineering solution based on a roller shock absorber with working surface in the form of a brachistochrone [10,16,32].The dynamic analysis of high-rise structures for wind forces deals with forced vibrations excited by pulsating wind pressure and self-excited vibrations such as wind resonance [1,3,4]. The principal natural frequencies of such structures are low, and the displacements of the upper parts of high-rise structures are great (1 to 3 m).…”
mentioning
confidence: 99%